2022
DOI: 10.1111/jdi.13950
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of textured insoles on the balance in patients with diabetic neuropathy

Abstract: Aims/Introduction Neuropathy is a common complication of diabetes that reduces balance by disrupting vision, and the sensory and vestibular systems. This is important in older adults who are more at risk of falling. Studies show that improving the sensory mechanisms through insoles can improve balance in people with balance disorders. As textured insoles have recently been considered for improving balance disorders, this study aimed to investigate the immediate effect of textured insoles on the balance of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Stolarczyk et al [56] reported an improvement in static balance among older patients (73 years old), suggesting encouraging outcomes in older pwDPN, which could be promoted in this population [15]. While it appears crucial to address proprioception through methods like unstable surfaces and conventional methods such as sensory stimulation of the sole of the foot and sensory FB [65], auditory and visual FB could play a pivotal role in improving static balance. This becomes particularly important as compensatory strategies involving vision and vestibular systems may be insufficient in pwDPN [66].…”
Section: Balancementioning
confidence: 99%
“…Stolarczyk et al [56] reported an improvement in static balance among older patients (73 years old), suggesting encouraging outcomes in older pwDPN, which could be promoted in this population [15]. While it appears crucial to address proprioception through methods like unstable surfaces and conventional methods such as sensory stimulation of the sole of the foot and sensory FB [65], auditory and visual FB could play a pivotal role in improving static balance. This becomes particularly important as compensatory strategies involving vision and vestibular systems may be insufficient in pwDPN [66].…”
Section: Balancementioning
confidence: 99%